2019
DOI: 10.1002/jobm.201800599
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐attached microorganism oxidation of ammonia in a hypereutrophic urban river

Abstract: To elucidate the importance and mechanisms of particle-attached microorganisms on ammonia oxidation, we conducted a controlled simulation experiment with samples collected from the Shunao River, an ammonia-rich hypereutrophic urban river in eastern China. The effects of particle concentration, ammonia concentration, organic carbon source and concentration, dissolved oxygen concentration, and pH were investigated on ammonia transformation rate (ammonia removal rate and NO 2 − + NO 3 − accumulation rate) andabun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
2
14
2
Order By: Relevance
“…Our results agree with previous research indicating that AOB communities are commonly tightly linked in ammonium-rich environments (Aalto et al, 2018;Hampel et al, 2018). These findings are also consistent with our previous study (Cai et al, 2019) and infer that AOB may play a more important role than AOA in this urban river network with high ammonia and low dissolved oxygen concentrations.…”
Section: Aoa and Aob Communities In The Hypereutrophic Urban River Networksupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with previous research indicating that AOB communities are commonly tightly linked in ammonium-rich environments (Aalto et al, 2018;Hampel et al, 2018). These findings are also consistent with our previous study (Cai et al, 2019) and infer that AOB may play a more important role than AOA in this urban river network with high ammonia and low dissolved oxygen concentrations.…”
Section: Aoa and Aob Communities In The Hypereutrophic Urban River Networksupporting
confidence: 93%
“…High riverine nitrogen pollution is a widespread problem in the Wen-Rui Tang River, as in much of China, due to rapid socio-economic development, urbanisation, and lagging waste/storm water collection and treatment (Lu et al, 2011). Water quality of the Wen-Rui Tang River is characterised by high ammonia (>2 mg N/L), low dissolved oxygen (<4 mg/L), and high turbidity (>20 NTU) (Cai et al, 2018(Cai et al, , 2019. Thus, there is a critical need for research examining ammonia transport and transformations in the Wen-Rui Tang River network to provide fundamental knowledge of microbial ecological functions for management and remediation of eutrophic urban river systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the high occurrence of OTU010/ASV0027/ASV0030 in KGF3_PA could be associated with the presence of highly liable POM (at KGF3) rather than contribution from the melt water inputs. Cai et al (2019) showed that members of MGI Ib, in particular, the genus Nitrososphaera of the family Nitrososphaeraceae were dominant in the particle-attached ammonia-oxidizing microbial communities. Recent studies have shown that particleattached MGI might be involved in the uptake and assimilation of ammonia (Li et al 2020) and organic compounds released via decomposition of organic particles (Alonso-Sáez et al 2012;Qin et al 2014).…”
Section: Phylogenetic Analysis Of Top 10 Otus and 20 Asvsmentioning
confidence: 99%
“…To sum up, although many research activities are currently conducted on the demolition of reinforced concrete structures, there are still many shortcomings that hinder wider use [18][19][20][21]. As a systematic crushing and dismantling method, microwaveassisted machinery is not only applicable to rock breaking [22,23] but can also be applied to the demolition in narrow urban spaces and to the demolition of special reinforced concrete structures. In the research on bond performance of reinforced concrete at high temperature, most specimens are heated in electric furnace at a slow heating rate and at low temperature gradient, and the corresponding results are mostly applied in fire protection [24].…”
Section: Introductionmentioning
confidence: 99%